(untitled) (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
Statistical literacy is an essential component of research literacy demanded for the research students to master as they are required to read, comprehend, and evaluate research articles. Misinterpretations of data and research findings are among the unfavorable results in the lack of research literacy. Consequently, it will affect the quality of their research and eventually leads to ripple impact on other researchers. However, this study is still under researched especially among postgraduate research students. Therefore, this paper examined statistical literacy level among postgraduate research students. This study was a survey conducted with a sample of 236 education postgraduate research students by using a set of statistical literacy items. The data were analysed using Rasch Analysis approach which includes item and person measures. Findings suggested that postgraduate students‘ statistical literacy level is at Moderate Low level. The findings also revealed that the hardest items to be answered by the students are related to hypothesis testing (significant value). In order for students to improve their statistical literacy, this study suggested that the instructors and institutions to reexamine and to explore new methods of teaching and learning statistics.